Interspecies and intraspecies genetic diversity of Ongole Grade cattle and Madura cattle based on microsatellite DNA markers - SUTARNO SUTARNO; NINA KURNIANINGRUM; ELISA HERAWATI; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2018)
Sutarno, Kurnianingrum N, Herawati E, Setyawan AD. 2018. Interspecies and intraspecies genetic diversity of Ongole Grade cattle and Madura cattle based on microsatellite DNA markers. Biodiversitas 19: 1593-1600. DNA microsatellite has been extensively employed for estimating the degree of kinship between genotypes and improving the quality of cattle products. Microsatellite markers are short-patterned DNA sequences and repeated tandem (sequentially) with 2-5 nucleotide units scattering the entire genome. The purpose of this study was to investigate the genetic characteristics of inter and intraspecies of Ongole Grade cattle and Madura cattle using microsatellite DNA markers. Blood samples from 20 individuals of each species were extracted by the method referring to Wizard Genomic DNA Purification Kit (Promega, USA) and PCR amplification was performed using 5 microsatellite loci, i.e., BM1824, ETH225, INRA005, MM12, and TGLA227. Results of the genetic characteristics of both species were calculated using the POPGENE program version 1.31. The data suggest that there is a genetic diversity of inter and intraspecies of Ongole Grade cattle and Madura cattle. The average value of Shannon's Information Index (I) at all microsatellite loci for Ongole Grade cattle was 0.76 and for Madura cattle was 1.12. Meanwhile, the average interspecies I value was 1.03. The mean intraspecies Polymorphic Information Content (PIC) of Ongole Grade and Madura cattle was 0.43, and 0.63, respectively, and the mean interspecies PIC value was 0.57. The data altogether suggest that all loci meet the standards as being informative markers in the assessment of genetic population because it has a PIC value> 0.5 especially for intraspecies of Madura cattle.